2015
DOI: 10.1016/j.coastaleng.2014.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of overtopping roughness factors for concrete armor units in non-breaking conditions using the CLASH database

Abstract: Elsevier Molines, J.; Medina Folgado, JR. (2015). Calibration of overtopping roughness factors for concrete armor units in non-breaking conditions using the CLASH database. Coastal Engineering. 96:62-70.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 9 publications
2
47
0
Order By: Relevance
“…(2)-type overtopping estimator. Molines and Medina (2015) analyzed different overtopping estimators for CMBW and found that the CLASH NN estimator had a far superior performance compared to Eqs. (2) to (4) and Eq.…”
Section: Overtopping Formulasmentioning
confidence: 99%
See 4 more Smart Citations
“…(2)-type overtopping estimator. Molines and Medina (2015) analyzed different overtopping estimators for CMBW and found that the CLASH NN estimator had a far superior performance compared to Eqs. (2) to (4) and Eq.…”
Section: Overtopping Formulasmentioning
confidence: 99%
“…Two sets of data corresponding to CMBW were considered from the CLASH database For perpendicular wave attack (β=0 o ), the data filter applied was the same as that detailed by Molines and Medina (2015): β=0 o ; cotαd=cotαu=cotα; 1.19 ≤cotα ≤ 4; B=0; tanαb=0; hb=0; CF (Complexity Factor)=1; RF (Reliability Factor)≤2; non-breaking conditions and Q>10 -6 .…”
Section: Overtopping Tests Considered In the Present Studymentioning
confidence: 99%
See 3 more Smart Citations